ELECTRONIC TEXTBOOK FOR AMATEUR ASTRONOMERS AND STUDENTS "Binary stars and their evolution" - Chinarova, L. L. (Одеські астрономічні публікації, 2017)
Electronic textbook for members and supervisors of the Youth Academy of Sciences; schoolars and teachers; students of the first courses. Total volume of the printed version is 86pp. The textbook is devoted to 100-th Anniversary of Prof. V.P.Tsessevich (1907-1983). It contains the chapters: "Birth and Life of Stars"; "Main Types of Binary Stars and Their Characteristics"; "Complex Interactions in Close Binary Stars"; "Evolution of Binary Stars"; "Symbiotic Stars"; "Cataclysmic Variables"; "Literature". This textbook (in Russian) is freely accessible at the Internet site http://chinarova.pochta.ru.